Genetic Diversity of HLA Class I and Class II Alleles in Thai Populations: Contribution to Genotype-Guided Therapeutics - Satapornpong, Patompong; Jinda, Pimonpan; Jantararoungtong, Thawinee; Koomdee, Napatrupron; Chaichan, Chonlawat; Pratoomwun, Jirawat; Na Nakorn, Chalitpon; Aekplakorn, Wichai; Wilantho, Alisa; Ngamphiw, Chumpol; Tongsima, Sissades; Sukasem, Chonlaphat (Frontiers in Pharmacology, 2020)
Human leukocyte antigen (HLA) class I and II alleles encodes several molecules that play role in the human immune system. There were found the association of HLA alleles and drug-induced cutaneous adverse reactions. The aim of this study was to investigate HLA class I and II alleles distribution in five regions of Thailand and to explore the relation of pharmacogenetic markers. HLA-A, -B, –C, -DRB1, -DQA1 and –DQB1 of 470 unrelated individuals Thai population were performed by polymerase chain reaction sequence-specific oligonucleotides probe (PCR-SSOs). Most frequency of HLA alleles in Thai population, including of HLA-A*11:01 (26.06%), -B*46:01 (14.04%), -C* 01:02 (17.13%), -DRB1*12:02 (15.32%), -DQA1*01:01 (24.89%) and -DQB1*05:02 (21.28%). The distribution of pharmacogenetic markers were different between Thai and other populations (African Americans, Caucasians, Hispanics, North American and Asians) consist of HLA-B*15:02, -B*13:01, -A*24:02, -A*33:03, -C*08:01, -C*03:02, -DRB1*12:02, -DRB1*16:02, -DRB1*13:02, -DRB1*15:02 and –DQB1*06:02. This first study of HLA class I and II database in five regions of Thailand. In addition, the database of HLA class I and II distribution might be compared with other ethnicity and support pharmacogenetic markers for screening prior before culprit drug administration.